2007
DOI: 10.1523/jneurosci.0459-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Human Cortical Areas for Reaches and Saccades

Abstract: Electrophysiological studies in monkeys have identified effector-related regions in the posterior parietal cortex (PPC). The lateral intraparietal area, for example, responds preferentially for saccades, whereas the parietal reach region responds preferentially for arm movements. However, the degree of effector selectivity actually observed is limited; each area contains neurons selective for the nonpreferred effector, and many neurons in both areas respond for both effectors. We used functional magnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
125
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(146 citation statements)
references
References 56 publications
20
125
1
Order By: Relevance
“…Just as recent studies in visual (Brewer et al 2005;Larsson and Heeger 2006;Sayres and Grill-Spector 2008;Arcaro et al 2009;Kolster et al 2010;Grill-Spector 2010, 2011;Rauschecker et al 2011), frontal (Hagler and Sereno 2006;Kastner et al 2007), and parietal cortex (Levy et al 2007;Swisher et al 2007) illustrate the benefit of multiple experimental techniques for clarifying the complexity of neural organization in both topographic and nontopographic areas, the present study demonstrates the generalizability of this approach to regions involved in multiple aspects of memory and attention. In particular, our results reveal heterogeneity across topographically organized PPC subregions, with 1) IPS0 displaying a distinct pattern of activity from IPS4, IPS5, and SPL1, and 2) IPS1-3 not exhibiting differential responses across retrieval conditions (though future studies with additional power are required to draw definitive conclusions about the relative effects of retrieval outcomes on responses in these areas).…”
Section: Dorsal Ppc: Lateral Ips Versus Splsupporting
confidence: 63%
“…Just as recent studies in visual (Brewer et al 2005;Larsson and Heeger 2006;Sayres and Grill-Spector 2008;Arcaro et al 2009;Kolster et al 2010;Grill-Spector 2010, 2011;Rauschecker et al 2011), frontal (Hagler and Sereno 2006;Kastner et al 2007), and parietal cortex (Levy et al 2007;Swisher et al 2007) illustrate the benefit of multiple experimental techniques for clarifying the complexity of neural organization in both topographic and nontopographic areas, the present study demonstrates the generalizability of this approach to regions involved in multiple aspects of memory and attention. In particular, our results reveal heterogeneity across topographically organized PPC subregions, with 1) IPS0 displaying a distinct pattern of activity from IPS4, IPS5, and SPL1, and 2) IPS1-3 not exhibiting differential responses across retrieval conditions (though future studies with additional power are required to draw definitive conclusions about the relative effects of retrieval outcomes on responses in these areas).…”
Section: Dorsal Ppc: Lateral Ips Versus Splsupporting
confidence: 63%
“…ROIs were analyzed only in the left hemisphere to account for the fact that participants used their right hand and foot (they obviously moved both eyes during saccades). In previous studies, ROIs V7, IPS1, and IPS2 were mapped using topographic mapping of saccades (i.e., their coordinates were functionally defined by eye movements) (Schluppeck et al, 2005;Silver et al, 2005;Hagler et al, 2007;Levy et al, 2007). V7 is located in Brodmann's area (BA) 19, whereas IPS1 and IPS2 lie anterior to V7 in BA 7.…”
Section: Fmri Data Analysismentioning
confidence: 99%
“…Neither region, however, appears to respond exclusively to either effector (Snyder et al, 1997;Andersen and Cui, 2009). Accordingly, research using functional magnetic resonance imaging (fMRI) in humans has revealed a large overlap of PPC activation during the planning of eye and hand movements (Beurze et al, 2007(Beurze et al, , 2009; Levy et al, 2007;Hinkley et al, 2009). However, biases for either eye or arm movements have also been shown in humans (Connolly et al, 2003;Medendorp et al, 2005;Connolly et al, 2007;Hinkley et al, 2009;Van Der Werf et al, 2010), and candidate homologs for macaque areas LIP and PRR have been proposed (Connolly et al, 2003;Schluppeck et al, 2005;Beurze et al, 2007;Hagler et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations